Analisis E-filing Direktorat Jenderal Pajak dan E-filing Online Pajak untuk Pengembangan Jasa Aplikasi Perpajakan (Studi Kasus di Indonesia) - Arniati, Arniati; Zodiansari, Putri; Kurniawan, Dedi (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2024)
Taxes play an important role in increasing Indonesia's economic growth which is indicated by 82.85% of funds for the State Revenue and Expenditure Budget originating from state tax revenues. The Directorate General of Taxes as the most important institution in Indonesia issued an e-filing tax administration system (Electronic Filing System). DGT is assisted by ASP in implementing e-filing to facilitate tax services to taxpayers. However, ASP's e-filing portal continues to decline, this attracts the author's attention to examine the existence of ASP's e-filing in the next few years. This study aims to find out the gaps in future application development so that it becomes an opportunity for e-filing taxes which Application Service Providers compare to e-filing at the Directorate General of Taxes. The research method used interviews. The results of this research indicate that the opportunity for ASPs e-filing is high for the next few years, this is indicated by the consultants who continue to use ASPs e-filing because there are several advantages of ASP's e-filing that DGT does not have.